Troubles at the Semantics/Syntax Interface: Some thoughts about the modal approach to conditionals - Schulz, Katrin (Proceedings of Sinn und Bedeutung, 2019)
Topic of the present paper is the modal approach to conditionals. We will distinguish two versions of the modal approach: a weak version which is the one that has been introduced by Kratzer (Kratzer (1977, 1979, 1981)) and a strong version that is the way the modal approach is presently used in many approaches to conditionals. In the second part of the paper we will present some arguments against the strong version of the modal approach. Aim of the paper is to stimulate a more critical and reflecting application of the modal approach.